ANALISIS KOMPETENSI GURU WALI KELAS TERHADAP PENGGUNAAN MEDIA AUDIO VISUAL PEMBELAJARAN SD - Aisyah Aisyah; Fitri Zuliana; Siti Aminah; Rizki Ananda (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this study was to analyze the competence of homeroom teachers towards the use of audio-visual media for elementary school learning. The research method used is a qualitative method. The type of qualitative research used in this research is descriptive using a qualitative descriptive approach. The results of the study show that the teacher's competency in using learning media is quite good, the teacher utilizes existing learning media such as learning videos from YouTube, but the teacher has not utilized and used learning media in each teaching and learning process, there are times when the teacher only gives assignments during learning.